The Incidence Of Miscarriage, Abortion, Or Miscarriage In Pregnant Women Of Risk And Non-Risk Age For Giving Birth In Health Services - Qudratullah, Fyzria; Gustiani, Ria; Sundari, Dona Tri; Leli, Leli; Treasa, Adisty Dwi; M, Warda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
One of the complications of spontaneous abortion is bleeding which if not treated quickly can increase maternal mortality rates. Vaginal bleeding is a common complaint that is often encountered and is a fairly high cause of a woman coming to the hospital, especially if it is known or suspected that there is a pregnancy. This study is a type of analytical survey, the design of this study is an observational analytical study with a cross-sectional approach. Samples were taken using a purposive sampling technique. The results of the cross-tabulation of the relationship between the age of pregnant women and the incidence of abortion obtained the results that at the age of pregnant women who are at risk, most experience abortion (92.3 % ), while the age of pregnant women who are not at risk mostly do not experience abortion (84.3%). The conclusion is that there is a fairly strong relationship between the age of pregnant women and the incidence of abortion of 0.592 (based on the Contingency Coefficient test).